PENGEMBANGAN MODUL Bryophyta DI KAWASAN AIR TERJUN BATU RAMBAT SEBAGAI SUMBER BELAJAR BIOLOGI - Rahmawati, Tika; Dewi, Asih Fitriana; Yudiyanto, Yudiyanto; Suhendi, Suhendi (Universitas Muhammadiyah Pontianak, 2022)
Student learning in the current era is very different from previous years, as a result of the COVID-19 pandemic, learning is shifted at home. Students must get used to not relying on the teacher so that they can try to make decisions and ways to solve problems individually. This change in learning makes students look for additional material to better understand learning even though learning is currently using distance learning. The development of new innovations in learning is currently very necessary. Creating learning resources can be done by utilizing the potential of the natural surroundings as well as introducing students to love the surrounding nature. One of the natural surroundings that has the potential as a source of learning in biology learning is the Batu Rambat waterfall in which there are Bryophyta (mosses) related to biological material. The purpose of this study was to develop the Bryophyta module in the Batu Rambat waterfall area as a learning resource for class X high school students based on the feasibility of the module with a small group trial limit. This study uses the Research and Development method with a 4D model carried out with the define stage, the design stage, the develop stage, and the disseminate stage. The results of the module feasibility test carried out by material expert validation obtained results of 91% with the